ANALISIS GERAKAN TENDANGAN BELAKANG PADA CABANG OLAHRAGA PENCAK SILAT (Studi pada Atlet Pusat Latihan Daerah Jawa Timur Kelas B Putra) - Heri Wahyudi, (Arena, 2013)
Abstract    The analysis of movement on sport is very important to done by coach or biomechanics expert to improve the wrong movement. Need to remember that all human movement is always connected with physics principals, and so do with the movement of back kick on pencak silat. Up till now, practically on the field, many athletes that done this movement still imperfect from the biomechanics side. Therefore the problem formulation that proposed in this research is how is the body segment, the amount of forces, and the amount of energy of kick to achieve a fast and exact kick? This research is purposed to knowing the angle of body segments, the amount of force and the amount of kick energy in order to achieve a fast and exact kick that done at PUSLATDA, so that can give suggestions to improve wrong movement. The type of this research is descriptive analysis with analysis technique that applying biomechanics principals and the measurement using the assists of software dart fish. The result that obtained from five kicks on research subject, found the quickest and fastest kick is done at fifth kick with kick speed as big as 126.11 m/s, with time 0.018s, and the amount of force that created is 14.19 N, energy that needed is 278315.31 J, with body inclination angle 160.50, and the angle of kick inclination is 145.30.  Keywords: back kick, analysis.